Effect of nano-hydroxyapatite filling on masticatory function and gingival sulcular fluid inflammatory factor levels in periapical inflammation - Honghui Xie; Aihong Tan; Zhijian Su; Chao Pan; Shuangjiang Li; Haibo Xiao (BioMedical Engineering OnLine)
Abstract Objective The purpose of this study is to investigate the influence of nano-hydroxyapatite (nano-HA) filling on the restoration of masticatory function and the modulation of inflammatory factors within gingival sulcular fluid in patients suffering from periapical inflammation. Methods 98 patients with periapical inflammation were selected and divided into a control group and a nano group using the red blue ball method, with 49 cases in each group. The control group was treated with conventional root canal therapy only, and the nano group underwent endodontic treatment with the nano-HA filling method. Gingival fluid samples were collected from all patients at enrollment, 1 week, and 3 months postoperatively to analyze the levels of interleukin- 1β (IL- 1β) and tumor necrosis factor-α (TNF-α). At the time of enrollment and 3 months after surgery, patients were monitored for bite force, masticatory efficiency, and clinical efficacy. Results In this study, compared to the control group, the experimental group treated with nano-HA filling showed significantly better improvement in bite force and masticatory efficiency, with the difference being statistically significant (P < 0.01). Moreover, the experimental group significantly inhibited the expression of inflammatory factors such as IL- 1β and TNF-α, with a continuous decrease in their levels over time. In terms of filling effect, healing rate, and total efficacy rate, the experimental group also achieved superior results compared to the control group, with the difference being statistically significant (P < 0.05). There was a negative correlation between the application of nano-HA fillers and the gingival sulcus inflammatory factor at 1 week postoperatively and 3 months postoperatively. Conclusion In comparison with conventional restorative materials, nano-HA restorative has been shown to possess several notable advantages. These include the promotion of recovery of masticatory function, the regulation of inflammatory factor expression in gingival sulcular fluid, and the enhancement of clinical efficacy and filling effect. This study provides a theoretical basis for the clinical promotion of the use of nano-HA restorative materials in the treatment of periapical inflammation.